2021
DOI: 10.3389/fcell.2021.635122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TCM on Tumor-Infiltrating Myeloid Precursors in the Tumor Microenvironment

Abstract: The tumor microenvironment (TME) is composed of tumor cells, blood/lymphatic vessels, the tumor stroma, and tumor-infiltrating myeloid precursors (TIMPs) as a sophisticated pathological system to provide the survival environment for tumor cells and facilitate tumor metastasis. In TME, TIMPs, mainly including tumor-associated macrophage (TAM), tumor-associated dendritic cells (DCs), and myeloid-derived suppressor cells (MDSCs), play important roles in repressing the antitumor activity of T cell or other immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Prior studies have noted that numerous traditional Chinese medicine and related active compounds have been reported to have potent anticancer properties ( 34 ). Sch B is the major anticancer monomer of lignans from the traditional Chinese medicinal herb S. chinensis Baill ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have noted that numerous traditional Chinese medicine and related active compounds have been reported to have potent anticancer properties ( 34 ). Sch B is the major anticancer monomer of lignans from the traditional Chinese medicinal herb S. chinensis Baill ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the tumour microenvironment by targeting these cells is an effective way to assist CAR-T-cell therapy. Liu J et al reviewed Chinese herbal medicine and its components that induce tumour cell apoptosis and directly inhibit tumour growth and invasion, providing new research ideas for cell therapy [ 163 ].…”
Section: Differentiation Effectmentioning
confidence: 99%
“…At present, fourth-generation CAR-T therapy has been extended. In this type of CAR-T-cell therapy, cytokine genes have been added to the structure, which can stimulate high cytokines expression that enhances the activity of T-cells after CAR-T-cells are activated, thereby improving the antitumour activity of CAR-T-cells [133] tumour growth and invasion, providing new research ideas for cell therapy [163].…”
Section: Car-tmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) could suppress the tumor cells proliferation, migration and invasion, induce cellular autophagy, stimulate apoptosis, block angiogenesis and improve the immunity of the body by altering the tumor microenvironment, thus acting as a comprehensive anti-tumor development and metastasis [ 6 , 7 ]. Several researches indicated that TCMs can be an effective supplemental strategy to adjuvant chemotherapy in the clinical treatment of CRC patients, and prolonged TCM therapy time can better improve the prognosis and survival rate of CRC patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%